2022
DOI: 10.1186/s10195-021-00622-7
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross-cultural adaptation, and validation of the Italian version of the anterior cruciate ligament–return to sport after injury (ACL-RSI) scale and its integration into the K-STARTS test

Abstract: Background The timing of a return to sport (RTS) after anterior cruciate ligament reconstruction (ACLR) represents a major subject of debate in sports medicine practice. Recently, the Knee Santy Athletic Return to Sport (K-STARTS) composite test was validated. This consists of a battery of physical tests and a psychological evaluation using the anterior cruciate ligament–return to sport after injury scale (ACL-RSI). This study aimed to translate the ACL-RSI and K-STARTS from English to Italian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This is supported by the personal reliability value of 0.75 (Figure 2(a)). At the same time, the consistency of the items used to measure students' research skills also showed very good quality [46], [47]. This fact is illustrated by the item reliability value of 0.96.…”
Section: Summary Statisticmentioning
confidence: 82%
“…This is supported by the personal reliability value of 0.75 (Figure 2(a)). At the same time, the consistency of the items used to measure students' research skills also showed very good quality [46], [47]. This fact is illustrated by the item reliability value of 0.96.…”
Section: Summary Statisticmentioning
confidence: 82%
“…The proportion of participants with concomitant injuries ranged from 0 to 89% amongst included studies [ 62 , 83 , 85 , 112 ]. The majority of studies included participants who were active in sport, either in preinjury competitive sport (38 original studies, 46%),[ 13 , 15 , 21 , 38 , 39 , 40 , 41 , 42 , 45 , 50 , 54 , 57 , 58 , 59 , 63 , 64 , 67 , 69 , 70 , 72 , 73 , 76 78 , 80 , 83 , 85 , 86 , 89 , 91 , 92 , 96 , 97 , 100 , 102 , 108 , 111 , 113 , 114 ], or recreational sport (10 original studies, 12%) [ 43 , 44 , 53 , 68 , 74 , 82 , 103 , 107 , 109 ]. Only one subgroup of participants in one study was classified as elite athletes [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is notable that several other tests have been developed and validated. 46,47 Future studies based on some other top questionnaires would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed; to draw more precise conclusions regarding non-surgical approach. It is notable that several other tests have been developed and validated 46,47 . Future studies based on some other top questionnaires would be beneficial.…”
Section: Accepted Manuscriptmentioning
confidence: 99%